(untitled) (Journal of Surgical Sciences, 2020)
Syringocystadenoma papilliferum is a rare skin tumour developing from eccrine or apocrine sweat gland. Though it usually appears in early life, it may occur in adult also. The clinical variants are plaques, linear and nodular. Head-neck region is affected most. Associations with naevus sebaceous, basal cell carcinoma or even squamous cell carcinoma have been described. Diagnosis is suspected clinically and confirmed by histopathology. Rapid growth, bleeding and ulceration indicate possible malignant transformation. Excision biopsy followed by reconstruction of the primary defect is the treatment of choice. Journal of Surgical Sciences (2018) Vol. 22 (2) : 139-141